PENGUSULAN PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN SEBAGAI PESERTA PEMILU MENURUT UNDANG-UNDANG PEMILIHAN PRESIDEN - Kadek Nanda Pratyahara,; Kadek Dedy Suryana,; Kadek Merry Herawati, (Nusantara Hasana Journal, 2024)
The presidential and vice-presidential elections in Indonesia are vital for the country's democratic process, impacting political stability and leadership selection. Regulated by Republic of Indonesia Law Number 42 of 2008, these elections transitioned from being decided by the People's Consultative Assembly (MPR) to direct public elections following the 1945 Constitution amendment. This shift has introduced challenges, particularly concerning political support requirements and independent candidate treatment. This research employs a combination of normative juridical and empirical methods, including legislative review, literature analysis, and interviews with key informants. The study uses a legislative and conceptual approach, drawing on primary, secondary, and tertiary legal materials. It investigates the role of the General Elections Commission (KPU) and law enforcement in addressing election violations such as money politics, using Election Case Decision Number 42/Pid.Sus/2019/PN LBO as a case study. Findings reveal difficulties in verifying political support and managing independent candidates, highlighting the need for legal and procedural improvements. To enhance electoral integrity and inclusivity, the research suggests reforms in the legal framework and election administration. These adjustments are crucial for achieving a more democratic and effective electoral process in Indonesia.